IMPACT OF JALABI ON THE TEACHING OF ISLAMIC STUDIES IN SENIOR SECONDARY SCHOOLS IN ILORIN METROPOLIS - Olalekan Rasheed Azeez; Ibrahim Solahudeen Owoyale-Abdulganiy; Ayuba Olaniyi Jibril; Usman Adisa Issa; Mikaeel Olayide Badmos (Taklim : Jurnal Pendidikan Agama Islam, 2023)
AbstractThe issue of Jalabi among teachers of Islamic studies in Ilorin metropolis is a socio-religious practice that needs to be properly scrutinized and checked due to the technicalities involved in the teaching-learning process, cultivation of good morals, discipline and character building which are the ultimate aims of the Islamic studies as enshrined in the National Policy on Education. The study examines the impact of Jalabi on the teaching of Islamic studies in senior secondary schools in Ilorin metropolis. A simple random sampling technique was used to sample 30 senior secondary schools across the three senatorial districts of the state and 260 teachers of Islamic studies as sampled in Kwara state. The researcher-designed questionnaire tagged “Impact of Jalabi on Teaching Islamic Studies Questionnaire (IJTISQ)” was used as an instrument for the study Descriptive statistics in the form of tables and percentages were used to describe the demographic data of the respondents and analyze the results obtained from the questionnaire administered. The results showed that a majority of respondents agreed that teachers who engage in Jalabi neglect regular teaching and that it hinders teachers' effectiveness. Additionally, most respondents disagreed that Jalabi practices lead to impressive teaching of Islamic studies. The survey also found that Jalabi practices prevent Islamic studies teachers from marking students' assignments, tests, and other tasks. However, only a small percentage of respondents agreed that teachers who practice Jalabi fail students arbitrarily. This implies that the practice of jalabi among senior secondary school teachers negatively affects the teaching of Islamic studies in Ilorin. It was concluded that the commercialization of Jalabi practices among senior secondary school teachers of Islamic studies hinders effective and efficient teaching of the subject in Ilorin metropolis, Kwara state, Nigeria. Keywords: Jalabi Doctrine, Islamic Studies Teachers, Islamic Cultural Identity